(untitled) (International Current Pharmaceutical Journal, 2015)
Chloroform and petroleum ether soluble fractions of the crude methanolic extract of the fruits of Baccaurea ramiflora (Lour.) have been investigated for the evaluation of cytotoxic and antioxidant activity. Brine shrimp lethality bioassay was used to evaluate the cytotoxic activity and free radical scavenging activity method was used to evaluate antioxidant activity. In brine shrimp lethality bioassay, the chloroform soluble fraction showed greater cytotoxic activity (LC50 value 74.2 µg/ml) than petroleum ether soluble fraction (LC50 value 129 µg/ml) compared to the standard drug vincristine sulfate (LC50 value 0.54 µg/ml). In free radical scavenging activity method (DPPH assay method), the chloroform soluble fraction showed greater antioxidant activity (IC50 value 49.78 µg/ml) than petroleum ether soluble fraction (IC50 value 75.31 µg/ml) compared to the standard antioxidant butylated hydroxytoluene (IC50 value 24.51µg/ml). This study reveals that Baccaurea ramiflora fruit possesses cytotoxic and antioxidant activity hence can be a potential source for the isolation of active principle(s) for different therapies. International Current Pharmaceutical Journal, May 2015, 4(6): 386-389